1998
DOI: 10.1038/sj.gt.3300740
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated gene transfer results in decreased lysosomal storage in brain and total correction in liver of aspartylglucosaminuria (AGU) mouse

Abstract: Aspartylglucosaminuria (AGU) is a lysosomal storage disexpression of AGA was demonstrated in the liver. The ease leading to mental retardation, which is caused by adenovirus vectors were also injected intraventricularly into deficiency of aspartylglucosaminidase (AGA). AGU is the brain of AGU mice resulting in AGA expression in the strongly enriched in the Finnish population in which one ependymal cells lining the ventricles, and further, diffusion major mutation called AGU Fin has been identified. The molof A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Several studies have shown that AAV-mediated gene transfer corrects neuropathology and, to a lesser extent, behavioral deficits in mouse models of neurometabolic disease (21)(22)(23)(24)(25)(26)(27). However, experiments in various lysosomal storage disease mouse models (e.g., mucopolysaccharidosis VII, infantile neuronal ceroid lipofuscinosis, and Sanfilippo type IIIB disease) have been primarily restricted to AAV serotypes 1 and 2 to mediate gene transfer in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that AAV-mediated gene transfer corrects neuropathology and, to a lesser extent, behavioral deficits in mouse models of neurometabolic disease (21)(22)(23)(24)(25)(26)(27). However, experiments in various lysosomal storage disease mouse models (e.g., mucopolysaccharidosis VII, infantile neuronal ceroid lipofuscinosis, and Sanfilippo type IIIB disease) have been primarily restricted to AAV serotypes 1 and 2 to mediate gene transfer in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…If neurons would maintain their capability to endocytose external enzymes during maturation, as suggested by our in vitro study, the new microglia population derived from BMT might produce sufficient amounts of enzyme to increase the enzyme activity of neurons to the level that exceeds the critical threshold and inhibits the formation of the damaging storage material in neurons. Recent in vivo gene therapy studies with the mouse model of AGU demonstrate that the AGA enzyme actually migrates from cell to cell also in the CNS tissue, which indicates that expression of AGA by a rather small population of neuronal cells may be sufficient to correct the CNS pathology (Peltola, et al, 1998). Although detailed in vivo studies will finally give answers to these important questions, continuous in vitro studies of the proteins in the most vulnerable cell types are required to provide a solid basis for developing therapeutic approaches for neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, Niemann-Pick disease type A (NPD-A) is a template for the development of genetic therapies for the neurological manifestations of other LSDs. Various vectors such as adenoviral (Peltola et al, 1998;Ziegler et al, 1999), lentiviral (Bosch et al, 2000;Kim et al, 2004), and adeno-associated viral (AAV) vectors have been used in a number of models of LSD (Barranger and Novelli, 2001;Hsich et al, 2002;Watson and Wolfe, 2003). The efficacy studies most relevant to the present work, however, have been those in which ASM À/À mice received intracerebral injections of an AAV vector encoding human ASM.…”
Section: Introductionmentioning
confidence: 95%